Kajian Kampanye Sosial Ambient Advertising WWF Turtle Soup Bowl - Alvanov Zpalanzani Mansoor; Nucky Artha (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
WWF Turtle Soup Bowl is WWF's campaign in response of decreasing sea turtle's population in Bali, Indonesia using outdoor ambient advertising. It won several awards, such as Best Use of Ambient Advertising: Stunts & Live Advertising on Spikes Asia and sixth place of Best Advertising on bestadsontv.com October 2008. The purpose of this research is to analyze Pros and Cons of Out-of-Home (OOH) advertising, focusing on the presentation and media usage. Research result shows that the pros of this campaign includes accessibility advantage by the placing it on Kuta Beach, Bali as a strategic tourism spot, effectively targeting audience with peculiar demographic and geographical aspects as the positive traits. Despite having several awards, this campaign has some notably least positive traits that makes the message delivery being less effective, which are difficulties on audience measurement and controlling the media, limited spot availability and geographical impact.